INCIDENCE AND ASSOCIATION OF SERUM HYPOMAGNESEMIA WITH FEBRILE SEIZURES IN YOUNG CHILDREN - AKRAM , MH; KHURSHID , A; MAZHAR , H (Biological and Clinical Sciences Research Journal, 2024)
Febrile seizures (FS) are a common occurrence in pediatric patients, affecting 2-5% of children between 6 months and 5 years of age. Various factors have been implicated in the pathogenesis of febrile seizures, including electrolyte imbalances such as hypomagnesemia, which can influence neuronal excitability and seizure susceptibility. Objective: The study aimed to assess the incidence of serum hypomagnesemia in children with febrile seizures and to examine the association between hypomagnesemia and the occurrence of febrile seizures. Methods: This retrospective case-control study was conducted at the Emergency Department of Shifa International Hospital from September 2023 to August 2024. A total of 300 children aged 6 months to 5 years were included in the study. Of these, 150 children presented with febrile seizures (case group), while 150 febrile children without seizures (control group) were selected as the comparison group. Patient data, including gender, body temperature, birth weight, age of onset, history of febrile seizures, gestational age, family history of seizures, and serum magnesium levels, were recorded. Serum magnesium levels were measured within 12 hours of a seizure episode, and results outside the reference range of 0.85-1.15 mmol/L were considered abnormal. Statistical analysis was performed using SPSS, and a Pearson correlation test was conducted to assess the association between serum magnesium levels and febrile seizures. Results: The mean serum magnesium level was significantly higher in the control group (0.99 ± 0.0957 mmol/L) than in the case group (0.95 ± 0.133 mmol/L) (p < 0.01). Hypomagnesemia was observed in 42 (28%) of the children with febrile seizures compared to 15 (10%) of the control group. A negative correlation was found between serum magnesium levels and the occurrence of febrile seizures (Pearson’s coefficient = -0.1709), indicating that lower magnesium levels were associated with a higher likelihood of febrile seizures. Conclusion: Children with febrile seizures exhibit significantly lower serum magnesium levels compared to febrile children without seizures. Hypomagnesemia appears to be associated with an increased risk of febrile seizures, particularly in those with a personal or family history of febrile seizures. Early identification and correction of hypomagnesemia in children presenting with fever may help in preventing febrile seizures.